Improvement in the dynamic responses of the semiempirical vehicle model using the Maxwell force model for the suspension forces. (December 2015) - Na, Sang-Do; Yoo, Wan-Suk
A multi-body vehicle model is more accurate than a lumped-mass model; however, it usually requires a cumbersome process to obtain accurate data for compliant elements such as bushings. To avoid this complex process associated with bushings or kinematic linkages, a semiempirical vehicle model was developed by switching the suspension characteristics to measured kinematic and compliance data. In a semiempirical vehicle model, it is assumed that the inertia effects in the suspension subsystem are ignored by replacing components of the suspension system with massless links. Although this semiempirical vehicle model is simple, it sometimes degrades the accuracy in the dynamic responses compared with those of the multi-body vehicle model. Thus, it is necessary to include the dynamic characteristics of the suspension in an semiempirical vehicle model to increase its accuracy. In this paper, a new technique is proposed that considers the dynamic effect of the suspension system in an semiempirical vehicle model by using the Maxwell force model. By comparing the vertical acceleration with that obtained by the proposed method, the dynamic responses with the semiempirical vehicle model become much closer to those of the multi-body vehicle model. The results show that the force with respect to the suspension's motion has a strong effect on the dynamic responses, and this relationship becomes important to improve the accuracy of the semiempirical vehicle model.